Immersive audio properties for NCL media elements - Diniz, Rafael; Moreno, Marcelo F. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
With the introduction of immersive audio formats like MPEG-H and Dolby AC-4, TV terminals may allow end users to configure their experience by changing values of audio parameters directly or indirectly (audio profiles) via some kind of configuration user interface. In order to support more dynamic user interfaces for this kind of interactive audio setup, DTV apps should be able to manipulate such parameters as well. This contribution proposes the addition of immersive audio properties to media elements in NCL applications.